Control of flow separation in a high-speed compressor cascade through acoustic excitation - Coskun, Seyfettin; Rajendran, David John; Pachidis, Vassilios; Bacic, Marko (American Institute of Aeronautics and Astronautics (AIAA), 2023)
The use of acoustic excitation for controlling flow separation in a NACA65-K48 linear compressor cascade operating at aircraft engine representative Ma = 0.67 and chord-based Re = 560,000 is investigated numerically. Improved Delayed Detached Eddy Simulation (IDDES) is used for numerical simulations. The linear compressor cascade passage under investigation is subject to severe secondary flows that are the fundamental loss mechanisms in axial compressors. Secondary flows such as corner separation cover a significant portion of the blade height of the linear compressor cascade (LCC) because of its low aspect ratio. These losses result in passage blockage which results in performance degradation. In the current study, the effect of external acoustic excitation on flow separation characteristics in the compressor passage is examined. The effectiveness of acoustic excitation is investigated for two main excitation parameters: excitation frequency and amplitude. The dominant frequencies in the uncontrolled flow frequency spectra are used as the initial excitation frequencies whilst a range of excitation amplitudes are considered. It has been observed that when the acoustic excitation is applied with a frequency in the range of the most dominant frequency in the uncontrolled flow and an excitation amplitude above a threshold amplitude, the flow field can be modulated substantially to recover the cascade performance.